The five minds of the modern strength and conditioning coach: The challenges for professional development - Jeffreys, I. (Strength and Conditioning Journal, 2014)
Strength and conditioning coaching is a complex compilation of acts drawing on multiple forms of knowledge. Coaches need to demonstrate a wide range of applied skills to be effective. While effective coaches appreciate the need to learn throughout their careers in order to improve, proper selection of worthwhile learning opportunities can be a daunting task. The purpose of this article is to examine and expand our understanding of effective strength and conditioning coaching using gardner's "5 minds" framework. A secondary purpose is to connect this framework to the literature in coach education for coaches to select corresponding learning opportunities.